The Intersection of Ethnic Origin and Religion: Two Middle Eastern Muslim Doctoral Students' Counternarratives in the West (International Journal of Multidisciplinary Perspectives in Higher Education, 2025)
International doctoral students experience many difficulties while pursuing their degrees in the West. Since they join the program with their intersectional identities, they experience problems related to adaptation. Studies for international doctoral students' experiences are available in the literature, yet they mostly focus on language, supervision, and adaptation to society and culture. Thus, a gap exists in the counternarratives of Middle Eastern Muslim students at the intersection of religious and ethnic identity. Here, we used counternarratives to tell our experiences through the intersection of our religious and ethnic identities. We concluded that airports are the sites of Islamophobia and xenophobia while higher education institutions are the camouflaged sites of Islamophobia and xenophobia.